Peningkatan Kualitas Limbah Bulu Ayam melalui Fermentasi dengan Efektif Mikroorganisme 4 (EM4) - Mirnawati Mirnawati (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The aims of the present experiment were to study the effect of substrate composition and time period of incubation on the nutrient composition of chicken feather meal fermented with EM4. The experiment using completely: randomized design was aranged in 3 x 3 factorial designs with there replicates. The treatment were substrate composition (A) (A1 100% feather meal + 0% rice bran, A2 90% feather meal + 10% rice bran, A3 80% feather meal + 20% rice bran), and time of incubation (B) (9,12 and 15 days). Parameters observed were crude protein, crude fiber, crude lipid and BETN. Results showed that there was no interaction (P>0,05) between substrate composition and time of fermentation on crude protein, crude fiber, crude lipid and BETN, substrate composition and time of incubation gave significantly (P<0,05) effect on crude protein, crude fiber, crude lipid and BETN of the fermented products. It was concluded that the optimum substrate composition and incubation time was found by using 80% feather meal + 20% rice brand and 15 days of incubation time, which gave the highest crude protein of 56,37% and low crude lipid of 23,95 % and crude fiber of 3,4 %.